2009
DOI: 10.1021/jp805868u
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cation Complexation on the Structure of a Conformationally Flexible Multiply Charged Anion: Stabilization of Excess Charge in the Na+·Adenosine 5′-Triphosphate Dianion Ion-Pair Complex

Abstract: We report a computational study of the conformationally and tautomerically flexible cation-dianion complex of Na(+) with doubly deprotonated adenosine 5'-triphosphate (ATP) using a hierarchical selection method. The method uses molecular dynamics to generate initial conformeric structures, followed by a classification process that groups conformers into five "families" to ensure that a representative sample of structures is retained for further analysis, while very similar conformational structures are elimina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 55 publications
(100 reference statements)
2
18
0
Order By: Relevance
“…Moreover, previous studies have shown that the [NTP-2H] 2À -and [NTP-H] 1Àspecies found in the condensed phase under acidic conditions can have a protonated nucleobase, 8,[25][26][27] while the nucleobases were found to be neutral in our experiments. These differences are in agreement with previous gas-phase studies, [29][30][31][32][33][34][35][36] and are due to the absence of interactions with water, metal cations or other nucleobases. The favoured deprotonation sites were found to be the aand b-phosphate groups, in agreement with studies of the acid-base properties of NTPs in aqueous solutions, which indicate that the g-phosphate is less acidic than the a and b phosphates.…”
Section: Irmpd Spectroscopic Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Moreover, previous studies have shown that the [NTP-2H] 2À -and [NTP-H] 1Àspecies found in the condensed phase under acidic conditions can have a protonated nucleobase, 8,[25][26][27] while the nucleobases were found to be neutral in our experiments. These differences are in agreement with previous gas-phase studies, [29][30][31][32][33][34][35][36] and are due to the absence of interactions with water, metal cations or other nucleobases. The favoured deprotonation sites were found to be the aand b-phosphate groups, in agreement with studies of the acid-base properties of NTPs in aqueous solutions, which indicate that the g-phosphate is less acidic than the a and b phosphates.…”
Section: Irmpd Spectroscopic Resultssupporting
confidence: 92%
“…28 Several experimental and theoretical studies have focussed on ATP in the gas phase. [29][30][31][32][33][34] Akola and Jones performed a density functional theory (DFT) study of ATP complexes with water and magnesium anions and determined the theoretical structures of isolated ATP and GTP. These structures have the base in the anti-conformation (to reproduce the condensed-phase structure), but the authors suggest that the syn-conformation may be more stable in the gas phase due to interaction between the nucleobase and the phosphate tail.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, among the available metallomacronutrients, Na(I), K(I), Mg(II) and Ca(II), in living systems, nature selected Mg(II) as the cofactor for the vast majority of enzymes that catalyze the breakage of (P)O-P(O) bonds. It appears important that experimental studies via XRD, MQMAS, ESIMS, Raman crystallography like those reported in Refs [10,[39][40][41][42], as well as theoretical studies like those reported in Refs 11,[43][44][45], are more and more performed on Mg(II)-NTPs and -NDPs species with the aim to shed light on the mobility of the metal on (di)triphosphate chain, on the role of free and metal bound water molecules, on the role of third molecules (mostly aminoacid residues) able to interact with the metal ions proximal to nucleotides and with nucleotides themselves. The structural role of the second divalent cation in biological systems that catalyze reactions on nucleotides (see for example Refs [46][47][48][49]), are worthy of more efforts too, on the basis of structure for 1 and 2 and of recent structures deposited in the PDB.…”
Section: Resultsmentioning
confidence: 96%
“…ATP, in the gas phase (thus isolated) is an important area of research, because it allows getting insight into their nature. [7,8] these anions is the gas phase conversion of the triphosphate to the trimetaphosphate and, to the best of our knowledge, has not yet been studied. It is worth mentioning that it has been suggested that adenosine 5′-trimetaphosphate may be involved in biological processes; [9] however, it has not been confirmed.…”
Section: àmentioning
confidence: 99%